Possible prediction of obesity‐related liver disease in children and adolescents using indices of body composition. - Johansen, Magnus Jung; Vonsild Lund, Morten Asp; Ängquist, Lars; Fonvig, Cilius Esmann; Holm, Louise Aas; Chabanova, Elizaveta; Thomsen, Henrik S.; Hansen, Torben; Holm, Jens‐Christian (Pediatric Obesity, 2022)
Summary: Background: Diagnosis of nonalcoholic fatty liver disease in children and adolescents currently requires advanced or invasive technologies. Objectives: We aimed to develop a method to improve diagnosis, using body composition indices and liver biochemical markers. Methods: To diagnose non‐alcoholic fatty liver disease, 767 Danish children and adolescents underwent clinical examination, blood sampling, whole‐body dual‐energy X‐ray absorptiometry scanning and proton magnetic resonance spectroscopy for liver fat quantification. Fourteen variables were selected as a starting point to construct models, narrowed by stepwise selection. Individuals were split into a training set for model construction and a validation test set. The final models were applied to 2120 Danish children and adolescents to estimate the prevalence. Results: The final models included five variables in different combinations: body mass index–standard deviation score, android‐to‐gynoid‐fat ratio, android‐regional fat percent, trunk‐regional fat percent and alanine transaminase. When validated, the sensitivity and specificity ranged from 38.6% to 51.7% and 87.6% to 91.9%, respectively. The estimated prevalence was 24.2%–35.3%. Models including alanine transaminase alongside body composition measurements displayed higher sensitivity. Conclusions: Body composition indices and alanine transaminase can be used to estimate non‐alcoholic fatty liver disease, with 38.6%–51.7% sensitivity and 87.6%–91.9%, specificity, in children and adolescents with overweight (including obesity). These estimated a 24.2%–35.3% prevalence in 2120 patients.